PENGEMBANGAN VIDEO MENGGUNAKAN APLIKASI CAPCUT PADA PEMBELAJARAN IPS MATERI PEDULI TERHADAP MAKHLUK HIDUPSISWA KELAS IV DI SDN NO 21/VI RANTAU SULI - Yulia Darniyanti; Tanti Arensi; Muhammad Subhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Education is the process of changing the attitudes and behavior of a person or group in an effort to mature humans. The problem in this study is the low student learning outcomes due to the lack of media. The aim of this research is to produce valid, practical and effective vidio capCut. This study uses the type of research and development (research and development). The ADDIE development model has five stages, namely: Analyze, Design, Development, Implementation, Evaluation. The type of data taken from video development using the CapCut application uses qualitative and quantitative data. The instruments used in this study, video capcut validation, video capcut practicality instruments, video capcut effectiveness instruments. data collection techniques used, namely, observation, interviews and documentation Analysis of data in research using analysis of validity, practicality and effectiveness. The results of this study are validation, practicality and effectiveness, so the following results can be obtained: The validity of the video capcut which is assessed by the validator, totaling 3 people, obtains a percentage of 93.33% in the very valid category, the video capcut is feasible to use and in accordance with the provisions of SDN 21VI Rantau difficult. in the very practical category, so based on this analysis it was concluded that the video using the CapCut application was very practical. Furthermore, the effectiveness assessed from the results of the ability test in social studies learning material caring for living things in grade IV SD obtained a percentage of 87.05% in the very Practicality is assessed from the teacher response questionnaire and student response questionnaire. The teacher response questionnaire was 100% in the very practical category, the student response questionnaire was 90.06%